Youtube And Film Viewing Among Students At Heritage Polytechnic, Eket: An Analysis - Brown, George Nathan; Ifeanyi Martins Nwokeocha (International Journal of Economics, Business and Innovation Research, 2026)
This study investigates the patterns, motivations, and implications of YouTube-facilitated Nollywood film viewing among students at Heritage Polytechnic, Eket. Employing a survey research design, data were collected from a representative sample of 357 students drawn from six purposively selected departments across three faculties. The study examined the extent of student engagement with YouTube, the factors influencing their preference for the platform over traditional film-viewing channels, and the implications of these viewing habits for the Nigerian film industry. Findings revealed that approximately 60% of students accessed YouTube daily or multiple times weekly, predominantly to watch full films and trailers, while interactive activities such as commenting and sharing were less common. Practical considerations, including affordability, ease of access, and content variety, emerged as the primary drivers of platform preference, whereas peer influence and educational motivations were less significant. The study also found that YouTube promotes cultural engagement, increases awareness of film quality issues, and provides opportunities for independent filmmakers, but simultaneously exposes students to unregulated and pirated content. Grounded in the Technological Acceptance Model and the Uses and Gratifications Theory, the research highlights the dual role of YouTube as both an enabler of accessible film consumption and a platform with potential challenges for content regulation. The findings underscore the need for filmmakers, regulators, and educational institutions to harness YouTube’s advantages while implementing strategies for content verification, media literacy, and industry sustainability.